Profile of Critical Thinking Skills of Grade XI Students related Inheritance - Jumrodah; Wahyuni, Sri; Sasmita (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2023)
The ability to think critically from student learning outcomes is one of the abilities that students need to have. This study aims to analyze and see the ability of students to understand material that has been taught in schools on inheritance material. This type of research is a type of quantitative research. The data collection technique used is the test instrument technique using questions made by linking to the material that has been taught. The research subject was students who had taken biology subjects in the inheritance sub-chapter with a sample number of students grade XI in one of the Aliyah Madrasah in Palangka Raya City for the 2022/2023 academic year. Analysis of the ability of the results of critical thinking skills is seen through the achievement of the final scores obtained by students. The results of the analysis of students' critical thinking skills show that less than 50% of students do not yet have the ability to think critically in understanding inheritance material. The ability to think critically about inheritance in students grade XI Aliyah Madrasah is still low, this is due to a lack of ability to analyze and conclude and decide actions related to inheritance. So an innovative model or media is needed to encourage material inheritance.